Compliance of physical activity guidelines depending on cutoffs points and gender in Spanish university students - Corella, C.; Rodríguez-Muñoz, S.; Abarca-Sos, A.; Zaragoza, J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The main objectives of this study were: a) study the levels of physical activity (PA), according to the different cutoffs points used and gender; b) analyze the compliance of different international recommendations for physical activity by gender and cutoff points. 95 university students, 33 men and 62 women (21, 96 years) wore accelerometers to assess their levels of PA using uniaxial and triaxial cutoffs points. Results indicated higher PA levels in men in vigorous intensity, not in moderate. A high percentage of the sample fulfills the recommendations for moderate PA, nevertheless, for vigorous PA, it is low. Analyzes of PA with triaxial cutoffs points are higher than the uniaxial ones, besides a greatest compliance of PA recommendations of Physical Activity Guidelines Advisory (2008) and World Health Organization (2010) recommendations are used.